The Use of Drones in Emergency Medicine: Practical and Legal Aspects - Anna Konert; Jacek Smereka; Lukasz Szarpak (Emergency Medicine International)
Unmanned aerial vehicles, also known as drones, can play a significant role in military and civil emergency medicine. The aim of the study was to present the real possibilities of using them in rescue operations and to provide examples from all over the world. Unmanned aerial vehicles can be applied to transport goods on demand, provide blood in urban areas, save sinking people, analyse the scale of damages, monitor large human gatherings, perform exploration activities, deliver blood samples and other analysis material, provide automated external defibrillators, support rescue operations and air transport, and perform agricultural activities. One must, however, be aware of the existing regulations regarding drone flights as an appearance of an unreported unmanned aircraft in the controlled space is identified worldwide as affecting aviation safety.